First Isolation of Pseudomonas aeruginosa from Ear Abscess of a Red-Eared Slider (Trachemys scripta elegans) - Acik, Mehmet Nuri; Unsald, Sami; Melek, Sule; Cetinkaya, Burhan (Kafkas Univ, Veteriner Fakultesi Dergisi, 2018)
This case report is the first of the isolation and identification of Pseudomonas aeruginosa in a female, one year old red-eared slider hospitalized at the Surgery Clinics of Veterinary Faculty, Bingol University, Turkey, for unilateral ear abscess. Susceptibility of the agent to several antibiotics was also tested.
Kırmızı yanaklı bir su kaplumbağasının kulak apsesinden pseudomonas aeruginosa’nın ilk izolasyonu
Keywords: Red-eared slider; Ear abscess; Pseudomonas aeruginosa